2014
DOI: 10.1590/s0370-44672014000100005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcination conditions on the physical and chemical characteristics of sugar cane bagasse ash

Abstract: The effect of calcination temperature and air flow on the content of organic material, morphology of particles, degree of crystallinity and the reactivity with lime solution of the sugar cane bagasse ash is evaluated. The results show that the long fibers of the bagasse and organic material are retained when calcination occurs without sufficient air flow. Calcining with forced air-flow breaks the fibers, removes organic material and produces fine particles at a temperature of 600ºC. The non-organic material ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
(21 reference statements)
5
22
0
Order By: Relevance
“…In summary, the high LOI, lower density, greater PSD, larger SSA (in comparison with CPC), simultaneous appearance of amorphous and crystalline phases, and variability of the the UtSCBA's shapes and sizes can be attributed to the variations of temperature and air flow during the bagasse's calcination process in the sugar mill, in accordance with results observed by other authors (24).…”
Section: Chemical and Physical Properties Of The Selected Utscbasupporting
confidence: 91%
See 2 more Smart Citations
“…In summary, the high LOI, lower density, greater PSD, larger SSA (in comparison with CPC), simultaneous appearance of amorphous and crystalline phases, and variability of the the UtSCBA's shapes and sizes can be attributed to the variations of temperature and air flow during the bagasse's calcination process in the sugar mill, in accordance with results observed by other authors (24).…”
Section: Chemical and Physical Properties Of The Selected Utscbasupporting
confidence: 91%
“…The amorphous phase in the UtSCBA was observed as a diffuse halo in the interval 2θ from 10° to 35°. This halo, which is characteristic of pozzolanic materials, suggests the presence of amorphous substances such as silica (6,8,15,24,(28)(29). The crystalline phases of quartz and cristobalite in the UtSCBA were detected; both phases have been reported by others (6,25,29).…”
Section: Chemical and Physical Properties Of The Selected Utscbasupporting
confidence: 59%
See 1 more Smart Citation
“…Table 5 presents the chemical composition of the SCBA RG in terms of the main oxides identified by XRF. The main oxide present in the ash was SiO 2 , followed by Al 2 O 3 and Fe 2 O 3 , in agreement with previous results [30,31]. The cumulative amount of these three oxides is 80.26%.…”
Section: Resultssupporting
confidence: 92%
“…The peaks can be associated with the crystalline phases of silicon dioxide. Previous results have also demonstrated the presence of quartz [30]: for instance, Cordeiro et al [31] found quartz and cristobalite in SCBA. Table 5 presents the chemical composition of the SCBA RG in terms of the main oxides identified by XRF.…”
Section: Resultsmentioning
confidence: 88%